Thermostability-based binding assays reveal complex interplay of cation, substrate and lipid binding in the bacterial DASS transporter, VcINDY. Issue 21 (12th November 2021) - Sampson, Connor D. D.; Fàbregas Bellavista, Cristina; Stewart, Matthew J.; Mulligan, Christopher
Abstract : The divalent anion sodium symporter (DASS) family of transporters (SLC13 family in humans) are key regulators of metabolic homeostasis, disruption of which results in protection from diabetes and obesity, and inhibition of liver cancer cell proliferation. Thus, DASS transporter inhibitors are attractive targets in the treatment of chronic, age-related metabolic diseases. The characterisation of several DASS transporters has revealed variation in the substrate selectivity and flexibility in the coupling ion used to power transport. Here, using the model DASS co-transporter, VcINDY from Vibrio cholerae, we have examined the interplay of the three major interactions that occur during transport: the coupling ion, the substrate, and the lipid environment. Using a series of high-throughput thermostability-based interaction assays, we have shown that substrate binding is Na + -dependent; a requirement that is orchestrated through a combination of electrostatic attraction and Na + -induced priming of the binding site architecture. We have identified novel DASS ligands and revealed that ligand binding is dominated by the requirement of two carboxylate groups in the ligand that are precisely distanced to satisfy carboxylate interaction regions of the substrate-binding site. We have also identified a complex relationship between substrate and lipid interactions, which suggests a dynamic, regulatory role for lipids in VcINDY's transport cycle.